The phagocytic synapse in distinguishing particulate and soluble stimuli - Underhill, David (Henry Stewart Talks, 2013)
The Phagocytic Synapse, The ability of Phagocytes to discriminate between particulate ligands and soluble ligands, The Dectin-1 "phagocytic synapse" as a model mechanism for how a surface receptor can distinguish between a particle and a soluble ligand